2020
DOI: 10.3390/rs12142182
|View full text |Cite
|
Sign up to set email alerts
|

Gas Emission Craters and Mound-Predecessors in the North of West Siberia, Similarities and Differences

Abstract: Detailed analysis of five gas emission craters (GEC) found in the north of West Siberia is presented. Remote sensing data used in the study is verified by field surveys. Previous studies show that all of the GECs were preceded by mounds 2 to 6 m high and 20 to 55 m in diameter. GECs initially were 20–25 m in diameter, which increased in the first years of their existence. GECs are found in various environmental (shrublands or moss-grass tundra) and geomorphic (river valley, terrace, slopes) conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 15 publications
2
33
0
1
Order By: Relevance
“…They showed Sentinel-1 scenes acquired in different years, compared them visually to optical Sentinel-2 scenes, and suggested that backscatter anomalies are related to zones of very thin or no ice which resulted from gas bubble inclusions within the ice. Pointner et al (2019) also suggested that the regions of low backscatter may be a result of up-welling gas released through the sediments, which might lead to local thinning of the ice or that eddies might cause a local thinning of the ice layer, which is similar to the cause of ice rings on lakes Baikal, Hövsgöl and Teletskoye reported by Kouraev et al (2019Kouraev et al ( , 2016.…”
Section: Introductionmentioning
confidence: 83%
“…They showed Sentinel-1 scenes acquired in different years, compared them visually to optical Sentinel-2 scenes, and suggested that backscatter anomalies are related to zones of very thin or no ice which resulted from gas bubble inclusions within the ice. Pointner et al (2019) also suggested that the regions of low backscatter may be a result of up-welling gas released through the sediments, which might lead to local thinning of the ice or that eddies might cause a local thinning of the ice layer, which is similar to the cause of ice rings on lakes Baikal, Hövsgöl and Teletskoye reported by Kouraev et al (2019Kouraev et al ( , 2016.…”
Section: Introductionmentioning
confidence: 83%
“…In the course of studies based on the interpretation of RS data, it was proven that before the blowouts and explosions of gas at the sites of the craters, there were positive relief forms that looked very similar to the perennial heave mounds (PHMs) widely known in various regions of the Arctic [6,8,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]40,42,43,[47][48][49][50][51][52]57,58,60,63,68]. In total, according to RS data, 7185 PHMs were found on Yamal alone [8,31,34].…”
Section: Introductionmentioning
confidence: 99%
“…This required research into possible models of the PHMs' formation, as well as their destruction during the explosion. Various models have been proposed and substantiated in the papers of the OGRI RAS authors [6,8,[21][22][23][24][25][26][27][29][30][31][32][33][34][35][36][37][38]68] and other scientists [40,42,43,47,[49][50][51][52]57,58,76].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…По состо-Таблица 1. Краткие характеристики ЦМР ArcticDEM по стрипам в районе объекта С1 [18]: по данным ЦМР они больше в плане на 35,4-37,8%, а по высоте -на 1,7-22%. За счет понижения рельефа местности в южном направлении кажущаяся высота бугра с южной стороны достигает 8 м. В 2014 г. здесь даже остаточная часть бугра с бруствером была около 5 м -в три раза выше роста человека, что хорошо видно на рис.…”
Section: новые технологии освоения арктикиunclassified